Measuring social influence and group formation during evacuation process - Balboa, Adriana; Cuesta, Arturo; Alvear, Daniel (Collective Dynamics, 2020)
Evacuees are likely to respond and move forming groups. However specific data about grouping is generally unavailable and the relationship between response and movement times and specific groupings are unknown. Using a simple method, we measure behavioural cohesion of occupants during evacuation processes. The case study involves using the method in a bus station, a sport centre and a library. Results suggest that proximity (visual/verbal contact) is an important factor but not decisive in the formation of evacuation groups. Social ties and whether occupants share a target and/or an activity before the alarm are also deemed to be important factors. This study provides an exciting opportunity to advance our knowledge of social influence and group formation during evacuation.